Analisis Perubahan Strategi Pembelajaran dari Kurikulum 2013 ke Kurikulum Merdeka di SMAN 14 Kabupaten Tangerang - Meidivia, Sefty; Navafiitria, Azzahra Dwenka; Nisa, Aina Zulfatun; Hilaliyah, Tatu (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The curriculum is a set of plans and arrangements regarding learning materials that serve as a guide in teaching and learning activities. Indonesia has experienced several curriculum changes, including the 1947, 1964, 1968, 1973, 1975, 1984, 1994, 1997, 2004, 2013, and Merdeka Curriculum. Given the importance of the concepts of curriculum and learning in the education system, efforts are needed to plan lessons that align with the material being taught. The relatively quick shift from the 2013 Curriculum to the Merdeka Curriculum has made many teachers feel unprepared for these changes. At SMA Negeri 14, the 2013 Curriculum is applied for grade 12, while the Merdeka Curriculum is implemented in grades 10 and 11